2017
DOI: 10.1200/jco.2017.35.15_suppl.4014
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab ± ipilimumab in pts with advanced (adv)/metastatic chemotherapy-refractory (CTx-R) gastric (G), esophageal (E), or gastroesophageal junction (GEJ) cancer: CheckMate 032 study.

Abstract: 4014 Background: In the phase 3 ONO-12 study, 3rd- or later-line nivolumab (N) monotherapy prolonged OS vs placebo in Asian pts with adv G/GEJ cancer (median OS, 5.3 vs 4.1 mo; HR, 0.63; P < 0.0001; ASCO-GI 2017, Kang YK et al. J Clin Oncol. 2017;35 (suppl 4S) [abstract 2]). The phase 1/2 CheckMate 032 study showed favorable clinical activity of N ± ipilimumab (I) in Western pts with adv CTx-R G/E/GEJ cancer (NCT01928394). We report updated long-term follow-up data of G/E/GEJ pts in CheckMate 032. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 0 publications
3
42
0
Order By: Relevance
“…ORR was higher in PD-1 ligand (PD-L1) positive patients than PD-L1 negative patients (15.5% vs. 5.5%). Checkmate 032 assessed the combination of two checkpoint inhibitors, nivolumab (PD-1 inhibitor) and ipilimumab (cytotoxic T-lymphocyte-associated protein 4 inhibitor), and showed that ORR for combination therapy in PD-L1 positive patients was 40%, which was higher than nivolumab monotherapy [52] . Interestingly, among 7 patients with high microsatellite instability (MSI-H) tumors in Keynote-059, ORR was 57% and the CR rate was 14.3%.…”
Section: Second/third Line Therapymentioning
confidence: 99%
“…ORR was higher in PD-1 ligand (PD-L1) positive patients than PD-L1 negative patients (15.5% vs. 5.5%). Checkmate 032 assessed the combination of two checkpoint inhibitors, nivolumab (PD-1 inhibitor) and ipilimumab (cytotoxic T-lymphocyte-associated protein 4 inhibitor), and showed that ORR for combination therapy in PD-L1 positive patients was 40%, which was higher than nivolumab monotherapy [52] . Interestingly, among 7 patients with high microsatellite instability (MSI-H) tumors in Keynote-059, ORR was 57% and the CR rate was 14.3%.…”
Section: Second/third Line Therapymentioning
confidence: 99%
“…In a phase II trial, ipilimumab was compared with BSC for patients who had received first-line chemotherapy that was not significantly superior in efficiency as maintenance therapy [43] . Comparing the efficiency of nivolumab as a single agent or in combination with ipilimumab was performed in phase I/II trial (checkmate-032) [44] . The nivolumab + ipilimumab group showed a relatively higher ORR than the nivolumab monotherapy group (14% with nivolumab monotherapy and 26% with nivolumab + ipilimumab).…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…Survival result is not published yet. The CheckMate 032 study showed that PD-1 inhibitor in combination with CTLA-4 inhibitor was active in EC, but most population is adenocarcinoma (13). The KEYNOTE-059 study showed that PD-1 inhibitor in addition to 5-FU and cisplatin is manageable safety as the first line therapy for gastric cancer (14).…”
mentioning
confidence: 99%
“…PD-L1 expression and microsatellite instability (MSI) are considered as potential biomarker so far (13)(14)(15). MSI-H being a very reliable biomarker but PD-L1 is a poor predictor of response in GI tumors.…”
mentioning
confidence: 99%
See 1 more Smart Citation